Influência de dinamizações de Mercurius solubilis em enzimas de defesa, crescimento da soja e no controle de Pratylenchus brachyurus - Müller, Mônica Anghinoni (2015)
The nematode Pratylenchus brachyurus known as nematode lesions, affects the soybean crop caused significant damage, this means that there is a need to develop alternatives that supply the control of pathogens by aggregating in productivity. Then the objective is to verify the influence of homeopathic Mercurius solubilis in different potencies in soybean plants and on control of the nematode. For this, three experiments were carried out in climatized greenhouse, testing the potencies of 6, 12, 24, 50, 100, 200 and 400CH (centesimal Hahnemannian) of Mercurius solubilis, ethanol 30% and healthy plants (untreated and not inoculated) were used as control treatment. The treatments were applied weekly from the V3 growth stage of soybeans. Three days after the first treatment, inoculation of nematodes was done. After 50 and 70 days after inoculation of the first and second experiment respectively, were made assessments of the aerial part height, stem diameter, number of pods per plant, dry weight of aerial part, dry weight of leaf + petiole + stem, dry mass of total pods, dry weight per pod, fresh weight of root, and were count juvenile, adults and eggs in the soil and in roots, and determined the reproduction factor (RF). In the third experiment, were quantified enzymes involved in secondary metabolism of plants, peroxidase (POX), phenylalanine ammonia lyase (PAL) and polyphenol oxidase (PPO). The sample of roots were taken at intervals of 0, 3, 7 and 14 days after treatment (DAT) and in the 3rd DAT, inoculation was made. In laboratory was conducted a experiment to evaluate in vitro motility and mortality, a distilled water solution containing 100 ml-1 juveniles and adults were placed in plastic container and add 7 mL of in vivo treatments tested at a dilution of 0.1%. The experiments were conducted in a randomized block design. The potencies 24CH, 50CH, 200CH and 100CH reduce the number of adults and juveniles in soil, as well as the reproduction factor, furthermore 100CH is able to interfere in the productive aspects, increasing 107.5% in the number of pods when compared to the control ethanol 30%, as well as dynamization 6CH and 12CH. To POX the enzymatic activity was higher for dynamizations 6CH, 100CH and 400CH, 3, 7 and 14 DAT respectively. The PAL activity presented increases of 79.93%, 80.72% and 84.10% in dynamizations 6CH, 12CH and 24CH respectively compared to control treatment, 3 DAT. 14 days after the first treatment, 400CH dynamization showed an increase in the enzymatic activity of 53.41% and 32.21% when compared to the control ethanol 30% and absolute control respectively. The dynamization 24CH when compared to absolute control showed an increase of 41.10% in the enzymatic activity. So Mercurius solubilis may be a potential alternative for the control of the nematode